Institutional Aspects of Portugal-Spain Cross-Border Cooperation. - Podadera-Rivera, Pablo; Calderón-Vázquez, Francisco José (Taylor and Francis Group, 2018)
The Portuguese-Spanish border perfectly embodies the common characteristics of European cross-borders territories with a present which is characterised by abundant initiatives of cross-border cooperation. In the present paper we will analyse the institutional aspects of the cross-border cooperation on the Spanish-Portuguese border from its configurative elements: starting from the normative tools which have promoted it, up to the new institutions which have developed it; its results relating to the deactivation of the cross-border discontinuity and the minimization of inherent transaction costs due to the cross-border factor. The final conclusions of research reveal an important impact of the cross-border cooperation, of its institutions and tools in the political and administrative landscape of Portuguese-Spanish cross-border areas even though they are impregnated by excessive Community bureaucracy and with important administrative, fiscal and juridical-legal limitation.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/20463
Keywords: Cooperación europea; Unión Europea - Política regional; Institutions; Cross-Border Cooperation; European Union; Borderlands